Peningkatan Kapasitas Pelaporan Keuangan Bumdesa Gesang SejahteraÂ Desa Gesang Kecamatan TempehÂ Kabupaten Lumajang - Setyobakti, Moh. Hudi (IMPOWERMENT SOCIETY, 2018)
Business Unit of Village Unit or Bumdesa is mandate of Law no. 6 Year 2014 on the Village. The establishment of BUMDesa is an effort to accommodate all activities in the field of economy and / or public services managed by the village and / or inter-village cooperation. The regulation on BUMDesa is regulated through Village Regulations. Bumdesa Gesang Sejahtera was established in 2017, with a legal umbrella of village law. The effort developed by Bumdesa is based on the potential of agriculture and other sectors that have become embryos before. Businesses managed by Bumdesa include; (1) agriculture with organic rice production and fertilizer business, organic agricultural medicine, (2) waste transportation services, (3) HIPPA water service. The problem faced by Bumdesa Gesang Sejahtera as a partner is not yet optimal financial management Bumdesa, which consists of planning, implementation, administration and financial accountability. The pressing issue is financial administration, where Bumdesa has not been able to present financial reports and report to the Village Government. Devotion is done, is training and mentoring activities on (1) standardization of financial format, (2) process of preparation of financial statement, (3) OJT prepare financial report. The output of this devotion is the management capability for the operational operators in the process of administration and financial reporting Bumdesa covers the aspects of cognitive, psychomotor and affective.